Tau: From research to clinical development. Issue 10 (3rd May 2016) - Holtzman, David M.; Carrillo, Maria C.; Hendrix, James A.; Bain, Lisa J.; Catafau, Ana M.; Gault, Laura M.; Goedert, Michel; Mandelkow, Eckhard; Mandelkow, Eva‐Maria; Miller, David S.; Ostrowitzki, Susanne; Polydoro, Manuela; et al.
Abstract: Alzheimer's Association Research Roundtable Fall 2015—Tau: From research to clinical development. Tau pathology is recognized as the key driver of disease progression in Alzheimer's and other neurodegenerative diseases. Although this makes tau an attractive target for the development of novel diagnostic and therapeutic strategies, the mechanisms underlying the onset and progression of tau‐related neurotoxicity remain elusive. Recent strides in the development of sophisticated preclinical models and the emergence of tau PET imaging and fluid biomarkers provide new opportunities to increase our understanding of tau biology, overcome translational challenges, and accelerate the advancement of tau therapeutics from bench to bedside. With this in mind, the Alzheimer's Association convened a Research Roundtable in October 2015, bringing together experts from academia, industry, and regulatory agencies to discuss the latest understanding of tau pathogenic pathways and review the evolution of tau therapeutics and biomarkers currently in development. The meeting provided a forum to share experience and expertise with the common goal of advancing the discovery and development of new treatment strategies and expediting the design and implementation of efficient clinical trials.